- #71
ehild
Homework Helper
- 15,542
- 1,917
A is correct. Check the signs in the numerator for B. I got the opposite. I will check my derivation.
I didn't find any error upon looking at my derivation- I'll check it once moreehild said:A is correct. Check the signs in the numerator for B. I got the opposite. I will check my derivation.
It is OK, the mistake was at my side.Sho Kano said:I didn't find any error upon looking at my derivation- I'll check it once more
Got it. So now I just plug A and B into these equations and that is the answer right?ehild said:It is OK, the mistake was at my side.
Remember, a3=A. See the picture in post #56Sho Kano said:Got it. So now I just plug A and B into these equations and that is the answer right?
a1 = -A-B
a2 = -A+B
2a3 = a1+a2
Gotcha, won't believe how happy I was to see that the denominators of A and B were the same so I could easily put them togetherehild said:Remember, a3=A. See the picture in post #56
Congratulation! Now it is easy to answer the other questions.Sho Kano said:Gotcha, won't believe how happy I was to see that the denominators of A and B were the same so I could easily put them together
No, why do you think it? You have the expression for a3=A. What follows from it?Sho Kano said:For the 3rd question, would this be the right answer?
m3 = m1 + m2
A = a3 = 0ehild said:No, why do you think it? You have the expression for a3=A. What follows from it?
Yes, what does it mean for m3?Sho Kano said:A = a3 = 0
thus, m1m3g+m2m3g−4m1m2g = 0
After solving for m3 for that equation, that would be the answer for question 3.ehild said:Yes, what does it mean for m3?
Use that A=0, so a1 = -B and a2 = B. Plug in the expression for m3 into B.Sho Kano said:After solving for m3 for that equation, that would be the answer for question 3.
Then for question 4, I'd just plug in that into the m3's of a1 and a2 right?
Gotcha, so it goes like this right?ehild said:Use that A=0, so a1 = -B and a2 = B. Plug in the expression for m3 into B.
Yes, what do you get?Sho Kano said:Gotcha, so it goes like this right?
3) m1m3g+m2m3g−4m1m2g = 0 ; solve for m3
4) a1 = -B ; a2 = +B ; plug in m3 from (3)
m3 = 4m1m2/m1+m2ehild said:Yes, what do you get?
It would be good if you had not forgot parentheses. m3 = 4m1m2/(m1+m2).Sho Kano said:m3 = 4m1m2/m1+m2
B = (m2g - m1g) / (m1 + m2)ehild said:PARENTHESES!
On second thought, why is a3 = A?ehild said:No, a3=A
Depends on conventions! If all accelerations are positive up then a3 and A will have opposite signs, but if A is positive up and a3 is positive down they will have the same sign.Sho Kano said:On second thought, why is a3 = A?
a3 is down, while A is upwards
So because originally, I specified downwards as positive, that's why a3 is positive.haruspex said:Depends on conventions! If all accelerations are positive up then a3 and A will have opposite signs, but if A is positive up and a3 is positive down they will have the same sign.
Look at the figure in Post # 56, 'A' was how the rope around the upper pulley accelerated along its length. It was said that the pulleys move clockwise. The rope moves with the pulley, so the right piece of it moves downward, and the left piece moves upward. The rope must keep its length! A is the magnitude of acceleration of all points of the rope.Sho Kano said:On second thought, why is a3 = A?
a3 is down, while A is upwards
See post 70, a1 = -A-B, a2 = B-A, a3 = AAnjum S Khan said:What are the answers ?